2023
DOI: 10.1093/hr/uhad025
|View full text |Cite
|
Sign up to set email alerts
|

SlZF3 regulates tomato plant height by directly repressing SlGA20ox4 in the gibberellic acid biosynthesis pathway

Abstract: Plant height is an important target trait for crop genetic improvement. Our previous work has identified a salt-tolerant C2H2 zinc finger, SlZF3, and its overexpression lines also showed a semi-dwarf phenotype, but the molecular mechanism remains to be elucidated. Here, we characterized the dwarf phenotype in detail. The dwarfism is caused by the decrease of stem internode cell elongation and deficiency of bioactive gibberellic acids (GAs), which can be rescued by exogenous GA3 treatment. Gene expression assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…These results suggest that ZFP245 might promote the tolerance of rice to cold and drought by regulating the proline level and reactive oxygen species (ROS) scavenging capacity. Luo et al [ 12 ] found that SlZF3 regulates plant height by directly inhibiting genes in the gibberellin biosynthesis pathway.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that ZFP245 might promote the tolerance of rice to cold and drought by regulating the proline level and reactive oxygen species (ROS) scavenging capacity. Luo et al [ 12 ] found that SlZF3 regulates plant height by directly inhibiting genes in the gibberellin biosynthesis pathway.…”
Section: Introductionmentioning
confidence: 99%